Predominant factors that affect the environment due to the use of furanium resin in molds for metal smelting - Del Valle Jurado, Carlos (2021)
The research starts from the analysis of data obtained from objective situations, generated by volatile organic compounds in routine molding and casting operations in order to determine the predominant factors that affect environmental quality due to the use of furan resin in the preparation of molds for the manufacture of cast parts that is based on the principle of complying with the objectives proposed in the environmental protection regulation that regulates the development of activities in the manufacturing industry, as well as analyzes such activities during the production process in the manufacture of parts mentioned, assuming and verifying the environmental impacts that are generated in the previously determined area of ​​direct influence, proposing preventive measures that mitigate and correct the possible deviations in the processes that alter the balance of the physical and biological environment and of socioeconomic relations with the areas of influence. The development of the work was done taking as a reference with representative samples of the processes of manufacture of molds and metal casting, in an industrial area classified and authorized for this purpose, in which various types of pieces are made for the national industry. National legal standards and international standards were considered in general, as well as specifically, applicable to the generation of volatile organic compounds to analyze the productive processes of a foundry plant, the processes, sequence and activities that are developed in the manufacturing processes.